Product Optimization and Antimicrobial Efficiency of Starch-Based Active Packaging Film Prepared Using Amira (Plumbago Zeylanica) Root Extract. (6th September 2022) - Muche, Melak; Zegeye, Adamu; Lemma, Hirut; Gisila, Tilahun
Abstract : This study aimed to develop food packaging from cornstarch combined with methanol extract of Plumbago zeylanica root as antimicrobial agents. The antimicrobial activity of the extract was tested against three bacterial strains, namely, Staphylococcus aureus, Salmonella typhi, and Escherichia coli and one fungal strain called Aspergilla niger . Microorganism growth inhibition was examined by employing a zone of inhibition check on solid media. Two hundred microliters of assorted concentrations (200 mg/ml, 100 mg/ml, 50 mg/ml, and 25 mg/ml) of plant extracts were added into an eight-millimeter hole diameter employing a micropipette. Hence, 200 µl of 200 mg/ml extract inhibited 13.5, 8.75, 10.5, and 27 mm diameter for S . typhi, E . coli, S . aureus, and A . niger, respectively. The minimum inhibitory concentrations 1.25 mg/ml, 2.5 mg/ml, 1.25 mg/ml, and 0.625 mg/ml of crude extract utterly suppressed the growth of S . aureus, E . coli, S . typhi, and A . niger, respectively. Later on, the antimicrobial agent films and the control media were prepared by the casting method. The prepared antimicrobial packaging films exhibited inhibitory zones (a wide clear zone on solid media) for S . typhi and A . niger growth inhibition; however, inhibitions for E . coli and S . aureus were not effective. Antimicrobial activity decreased while decreasing the solubility of the film and antimicrobial concentration with increasing cornstarch content in the solution. The tensile strength of the films increased with increasing antimicrobial content in the solution. Higher antimicrobial inhibition activity was found at a 1.5 glycerol/starch ratio, 1.5 gram content of P . zeylanica, and 0.5 mm film thickness. Generally, the plasticized cornstarch antimicrobial packaging film combined with P . zeylanica extract had a significant effect on the growth of each selected microorganism and the physical properties of the material (P  < 0.05). A preprint of this research has previously been uploaded to the Addis Ababa University database (Yirdaw et al. 2018). In this section, only the summary and updated content of the research findings are presented.